CHEKHOV AND SHOLOKHOV: REGULATED INTERSECTIONS - Marina Ch. Larionova (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2023)
Unregulated intersections, according to E.A. Yablokov, are artistic rapprochement of writers not connected to each other biographically. At first glance, the oeuvres of Chekhov and Sholokhov form such an unregulated intersection. However, it is seemingly unregulated, seemingly uncrossed. The article highlights the commonality of writers, who belonged to one ethno-cultural space. The author indicates the consilience of functions of the image of steppe in Chekhov’s short-stories and Sholokhov’s epic novel The Silent Don (Tikhy Don), the similarities and differences when it comes to the writers focus on the Cossacks and related issues. Thus, the comparison of the writers may be both within their typological commonality and genetic succession.